High Energy X-Ray Detection by MicroPattern Gaseous Detector - Saeedeh Khezripour; Mohammad Reza Rezai Rayeni (Frontiers in Biomedical Technologies)
Purpose: The paper aims to discuss the response of the Micro-Mesh Gaseous Structure (Micromegas) detector to high-energy X-ray with 2.3 MeV energy using photon to neutron converters in addition to optimization of the detector components by Monte Carlo simulation.